Fluororesin composition and molded body
Patent Information
- Application Number
- JP2023079293
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-03-31
- Filing Date
- 2023-05-12
- Publication Date
- 2025-04-08
AI Technical Summary
Polytetrafluoroethylene (PTFE) cannot be reused as a molding material after being heated above its melting point without achieving sufficient physical properties, limiting its handleability and reusability.
A fluororesin composition comprising a combination of fluororesin A, which has been heated above its melting point and lacks melt fluidity, and fluororesin B, polymerized by emulsion polymerization and also lacking melt fluidity, with specific density, melting point ranges, and modified monomer units, is used to create a molded article through compression molding and firing.
The composition provides excellent handleability and maintains tensile strength and strain, even when containing fluororesins heated above their melting point, resulting in high-quality molded articles.
Abstract
Description
[Technical Field]
[0001] This disclosure relates to fluororesin compositions and molded articles. [Background technology]
[0002] Polytetrafluoroethylene (PTFE) that has been heated to temperatures above its melting point for molding or other processing cannot be reused as a molding material without obtaining sufficient physical properties, and therefore its recycling for molding applications remains limited.
[0003] Patent documents 1 and 2 describe technologies for recycling PTFE that has been crushed after firing and heated PTFE. [Prior art documents] [Patent Documents]
[0004] [Patent Document 1] International Publication No. 2019 / 244433 [Patent Document 2] Japanese Patent Publication No. 2006-70233 [Overview of the project] [Problems that the invention aims to solve]
[0005] This disclosure aims to provide a fluororesin composition that is easy to handle despite containing a fluororesin that has been heated to a temperature above its melting point, and a molded article obtained from the above fluororesin composition. [Means for solving the problem]
[0006] This disclosure provides a fluororesin composition comprising fluororesin A, which has a history of being heated to a temperature above its melting point and does not exhibit melt fluidity, and fluororesin B, which has a history of being heated to a temperature above its melting point and is polymerized by emulsion polymerization and does not exhibit melt fluidity, and having an apparent density of 0.42 g / ml or more.
[0007] Fluororesin A is preferably polytetrafluoroethylene.
[0008] The above fluororesin composition preferably has one or more melting points in the temperature range below 333°C and one or more melting points in the temperature range of 333 to 360°C.
[0009] The above fluororesin composition preferably has an angle of repose of less than 40°.
[0010] The above fluororesin composition preferably has an average secondary particle diameter of 50 to 500 μm.
[0011] It is preferable that the content of the low molecular weight fluorine-containing compound is 1 ppm by mass or less relative to the above fluororesin composition.
[0012] The above fluororesin composition contains tetrafluoroethylene units and modified monomer units based on modified monomers copolymerizable with tetrafluoroethylene, and it is preferable that the amount of the modified monomer units is 1.0% by mass or less relative to the total polymer units.
[0013] The above fluororesin composition is preferably in powder form.
[0014] The above fluororesin composition preferably has a tensile breaking strength of 10 MPa or more.
[0015] The above fluororesin composition preferably has a tensile fracture strain of 150% or more.
[0016] The above fluororesin composition is preferably granulated.
[0017] The above fluororesin composition preferably further contains a filler.
[0018] This disclosure also provides molded articles obtained by compression molding and firing the above-mentioned fluororesin composition.
[0019] This disclosure also provides a fluororesin composition comprising a fluororesin A that does not exhibit melt flowability and has a history of being heated to a temperature above its melting point, and a fluororesin B that does not exhibit melt flowability and is polymerized by emulsion polymerization without a history of being heated to a temperature above its melting point, and also comprising tetrafluoroethylene units and modified monomer units based on modified monomers copolymerizable with tetrafluoroethylene.
[0020] The above fluororesin composition preferably has an apparent density of 0.42 g / ml or more. [Effects of the Invention]
[0021] According to this disclosure, it is possible to provide a fluororesin composition that is easy to handle despite containing a fluororesin that has been heated to a temperature above its melting point, and a molded article obtained from the above fluororesin composition. [Modes for carrying out the invention]
[0022] The following provides a detailed explanation of this disclosure.
[0023] This disclosure provides a fluororesin composition (hereinafter also referred to as the first fluororesin composition) comprising fluororesin A, which has a history of being heated to a temperature above its melting point and does not exhibit melt fluidity, and fluororesin B, which has a history of being heated to a temperature above its melting point and is polymerized by emulsion polymerization and does not exhibit melt fluidity, and having an apparent density of 0.42 g / ml or more. The first fluororesin composition contains fluororesin B polymerized by emulsion polymerization without a history of being heated to a temperature above its melting point, and its apparent density is within a specific range. Therefore, despite containing fluororesin A which has a history of being heated to a temperature above its melting point, it has excellent handling properties (e.g., handling properties during transportation and compression molding). Furthermore, the first fluororesin composition has good tensile properties (e.g., tensile fracture strength, tensile fracture strain).
[0024] The first fluororesin composition preferably has one or more melting points in the temperature range below 333°C and one or more melting points in the temperature range of 333 to 360°C. The temperature range below 333°C is more preferably below 332°C, even more preferably below 331°C, preferably 100°C or higher, more preferably 140°C or higher, and even more preferably 160°C or higher. The above temperature range of 333 to 360°C is more preferably 334°C or higher, even more preferably 335°C, even more preferably 355°C or lower, and even more preferably 350°C or lower. Having melting points in the two temperature ranges mentioned above indicates that the fluororesin composition includes fluororesin A, which does not exhibit molten fluidity after being heated to a temperature above its melting point, and fluororesin B, which does not exhibit molten fluidity and has not been heated to a temperature above its melting point.
[0025] Fluororesin A has a history of being heated to a temperature above its melting point. Examples of such heating include heating for molding, heat treatment, etc.
[0026] Fluororesin A preferably has a melting point of 100°C or higher and less than 333°C, more preferably less than 332°C, and even more preferably less than 331°C. The lower limit is not limited, but 140°C is more preferable, and 180°C or higher is even more preferable.
[0027] Fluororesin A preferably has one or more melting points in a temperature range below 333°C. The temperature range below 333°C is more preferably below 332°C, even more preferably below 331°C, and preferably 100°C or higher, more preferably 140°C or higher, and even more preferably 180°C or higher. A melting point within the above range indicates that the material has been heated to a temperature above its melting point. Fluororesin A may also have a melting point in the temperature range of 333°C or higher.
[0028] In this specification, the melting point of a fluororesin is the temperature corresponding to the minimum point in the heat of fusion curve obtained by differential scanning calorimetry [DSC] using an X-DSC7000 (manufactured by Hitachi High-Tech Science Corporation) at a heating rate of 10°C / min. If there are two or more minimum points in a single melting peak, each of them shall be considered a melting point.
[0029] Fluororesin A does not exhibit melt-flow properties. In this specification, "not exhibiting melt fluidity" means that the melt flow rate (MFR) is less than 0.25 g / 10 min, preferably less than 0.10 g / 10 min, and more preferably 0.05 g / 10 min or less. In this specification, MFR is a value obtained in accordance with ASTM D1238, using a melt indexer, as the mass (g / 10 min) of polymer flowing out of a nozzle with an inner diameter of 2.095 mm and a length of 8 mm per 10 minutes at a measurement temperature (e.g., 372°C for PFA and FEP, 297°C for ETFE) and load (e.g., 5 kg for PFA, FEP, and ETFE). In the case of PTFE, the value is obtained by measurement under the same measurement conditions as for PFA.
[0030] Furthermore, if a pre-molded body (unfired molded body) made by compression molding of fluororesin is heated at a temperature above the melting point of the fluororesin for one hour or more, and the decrease in thickness after heating compared to the thickness before heating is less than 20%, or if the thickness after heating is greater than the thickness before heating, it also means that the fluororesin does not exhibit melt-fluidity.
[0031] Polytetrafluoroethylene [PTFE] is preferred as the fluororesin A. The PTFE may be high molecular weight PTFE.
[0032] The PTFE as fluororesin A may be a homopolymer of TFE, or it may be a modified PTFE containing polymerization units based on 99.0% by mass or more of TFE and polymerization units based on 1.0% by mass or less of modified monomer (hereinafter also referred to as "modified monomer units"). The modified PTFE may consist only of polymerization units based on TFE and modified monomer units.
[0033] The above-mentioned modified PTFE preferably has a modified monomer unit content in the range of 0.00001 to 1.0% by mass relative to the total polymerization units. The lower limit of the modified monomer unit content is more preferably 0.0001% by mass, even more preferably 0.001% by mass, even more preferably 0.005% by mass, and especially preferably 0.010% by mass. The upper limit of the modified monomer unit content is preferably 0.90% by mass, more preferably 0.50% by mass, even more preferably 0.40% by mass, even more preferably 0.30% by mass, especially preferably 0.20% by mass, and particularly preferably 0.10% by mass. In this specification, the above-mentioned modified monomer unit means a part of the molecular structure of PTFE that is derived from the modified monomer.
[0034] The content of each polymerization unit mentioned above can be calculated by appropriately combining NMR, FT-IR, elemental analysis, and X-ray fluorescence analysis depending on the type of monomer.
[0035] The above-mentioned modified monomers are not particularly limited as long as they can copolymerize with TFE, and include, for example, perfluoroolefins such as hexafluoropropylene [HFP]; hydrogen-containing fluoroolefins such as trifluoroethylene and vinylidene fluoride [VDF]; perhaloolefins such as chlorotrifluoroethylene; perfluorovinyl ethers; perfluoroallyl ethers; (perfluoroalkyl)ethylene, ethylene, etc. Furthermore, one or more modified monomers may be used.
[0036] The perfluorovinyl ether mentioned above is not particularly limited, for example, the following general formula (A): CF2 = CF - ORf (A) Examples include perfluorounsaturated compounds represented by the formula (wherein Rf represents a perfluoroorganic group). In this specification, the term "perfluoroorganic group" means an organic group in which all hydrogen atoms bonded to a carbon atom are replaced with fluorine atoms. The perfluoroorganic group may have an ether oxygen.
[0037] Examples of the perfluorovinyl ethers mentioned above include perfluoro(alkyl vinyl ether) [PAVE] in which Rf in the general formula (A) above is a perfluoroalkyl group having 1 to 10 carbon atoms. The number of carbon atoms in the perfluoroalkyl group is preferably 1 to 5.
[0038] Examples of perfluoroalkyl groups in the above-mentioned PAVE include perfluoromethyl, perfluoroethyl, perfluoropropyl, perfluorobutyl, perfluoropentyl, and perfluorohexyl groups.
[0039] The above perfluorovinyl ethers are further defined as those in the above general formula (A) where Rf is a perfluoro(alkoxyalkyl) group having 4 to 9 carbon atoms, and where Rf is defined by the following formula:
[0040] [ka]
[0041] (In the formula, m represents an integer from 0 to 4.) The base is represented by the following formula, where Rf is:
[0042] [ka]
[0043] Examples include the base represented by (wherein n represents an integer from 1 to 4).
[0044] (Perfluoroalkyl)ethylene (PFAE) is not particularly limited and examples include (perfluorobutyl)ethylene (PFBE), (perfluorohexyl)ethylene, etc.
[0045] Examples of perfluoroallyl ethers include general formula (B): CF2 = CF - CF2 - ORf 1 (B) (In the formula, Rf 1 ) represents a perfluoroorganic group. Examples include fluoromonomers represented by ).
[0046] The above Rf 1 The perfluoroallyl ether is preferably a perfluoroalkyl group having 1 to 10 carbon atoms or a perfluoroalkoxyalkyl group having 1 to 10 carbon atoms. The perfluoroallyl ether is preferably at least one selected from the group consisting of CF2=CF-CF2-O-CF3, CF2=CF-CF2-O-C2F5, CF2=CF-CF2-O-C3F7, and CF2=CF-CF2-O-C4F9, more preferably at least one selected from the group consisting of CF2=CF-CF2-O-C2F5, CF2=CF-CF2-O-C3F7, and CF2=CF-CF2-O-C4F9, and even more preferably CF2=CF-CF2-O-CF2CF2CF3.
[0047] The PTFE used as fluororesin A preferably has a standard specific gravity (SSG) of 2.280 or less, more preferably 2.10 or less. It is also preferably 1.50 or more, and more preferably 1.60 or more. The SSG is measured using a sample molded in accordance with ASTM D 4895-89 and measured by the water displacement method in accordance with ASTM D-792.
[0048] The PTFE used as fluororesin A typically exhibits non-melt secondary processability. This non-melt secondary processability refers to the property of not being able to measure the melt flow rate at temperatures higher than the melting point, in other words, the property of not easily flowing even in the melting temperature range, in accordance with ASTM D-1238 and D-2116.
[0049] The PTFE (high molecular weight PTFE) used as fluororesin A preferably has one melting point of 310°C or higher, more preferably 320°C or higher, and preferably less than 333°C. It may also have a melting point in the temperature range of 333°C or higher.
[0050] The first fluororesin composition may contain particles of fluororesin A. The particles of fluororesin A may be secondary particles of fluororesin A.
[0051] The particles of the fluororesin A described above preferably have an average secondary particle diameter of 1 to 200 μm, in that the handling properties of the fluororesin composition are further improved. The average secondary particle diameter is more preferably 5 μm or more, even more preferably 10 μm or more, even more preferably 150 μm or less, even more preferably 100 μm or less, even more preferably 70 μm or less, particularly preferably 50 μm or less, and most preferably 30 μm or less. The above average secondary particle diameter is measured using a Beckman Coulter laser diffraction particle size distribution analyzer (LS13 320) in a dry manner at a vacuum pressure of 20 mH2O, and is defined as being equal to the particle diameter corresponding to 50% of the integrated particle size distribution (volume-based).
[0052] The particles of the fluororesin A described above preferably have a D90 of 10 μm or more, more preferably 30 μm or more, even more preferably 50 μm or more, and also preferably 600 μm or less, more preferably 500 μm or less, and even more preferably 400 μm or less, in order to further improve the handling properties of the fluororesin composition described above. The above D90 is measured using a Beckman Coulter laser diffraction particle size distribution analyzer (LS13 320) in a dry manner at a vacuum pressure of 20 mH2O, and is defined as being equal to the particle size corresponding to 90% of the integrated particle size distribution (volume-based).
[0053] The particles of the fluororesin A described above can be obtained, for example, by crushing the cutting chips of a molded product obtained by compression molding and firing a fluororesin that does not exhibit melting fluidity and has not been heated to a temperature above its melting point. The crushing can be carried out using a pulverizer or the like. After coarse crushing, it may be further refined into fine particles. The shape of the compression molded product is not particularly limited. The firing temperature should be above the melting point of the fluororesin. The pulverizer is not particularly limited and should be capable of pulverizing (preferably finely grinding) the cutting chips. Examples include air jet mills, hammer mills, force mills, stone mill type pulverizers, and freeze pulverizers.
[0054] The particles of fluororesin A described above can also be obtained by heating a fluororesin powder that does not exhibit melting fluidity and has not been heated to a temperature above its melting point, above its melting point without compression molding, and then grinding it using a pulverizer. The pulverizer is the same as described above.
[0055] Fluororesin B has no history of being heated to a temperature above its melting point.
[0056] The fluororesin B preferably has a melting point of 100 to 360°C. More preferably, the melting point is 140°C or higher, even more preferably 160°C or higher, even more preferably 355°C or lower, and even more preferably 350°C or lower.
[0057] Fluororesin B preferably has one or more melting points in the temperature range of 333 to 360°C. The above temperature range is more preferably 334°C or higher, even more preferably 335°C or higher, even more preferably 355°C or lower, and even more preferably 350°C or lower. The fact that the melting point is within the above range indicates that there is no history of heating to a temperature above the melting point. In addition to the melting point mentioned above, the substance may also have a melting point in the temperature range below 333°C.
[0058] Fluororesin B does not exhibit melt flowability. The melt flowability is as described above.
[0059] PTFE is preferred as the fluororesin B. The PTFE may be high molecular weight PTFE.
[0060] The PTFE (high molecular weight PTFE) used as fluororesin B preferably exhibits at least one endothermic peak in the range of 333 to 347°C in the heat of fusion curve when heated at a rate of 10°C / min using a differential scanning calorimeter (DSC), and the heat of fusion at 290 to 350°C calculated from the heat of fusion curve is preferably 62 mJ / mg or more.
[0061] The PTFE used as fluororesin B preferably has a standard specific gravity (SSG) of 2.130 to 2.280. The standard specific gravity is measured using a sample molded in accordance with ASTM D4895 89 and the water displacement method in accordance with ASTM D 792. For PTFE that has not been heated to a temperature above its melting point, "high molecular weight" means that the standard specific gravity is within the range mentioned above.
[0062] The PTFE used as fluororesin B typically exhibits non-melt secondary processability. The non-melt secondary processability is as described above.
[0063] The PTFE used as fluororesin B may be a homopolymer of TFE, or it may be a modified PTFE containing polymerization units based on 99.0% by mass or more of TFE and polymerization units (modified monomer units) based on 1.0% by mass or less of modified monomer. The modified PTFE may consist only of polymerization units based on TFE and modified monomer units. Modified PTFE is preferred because it further improves the handling properties and tensile strength of the fluororesin composition.
[0064] The above-mentioned modified PTFE preferably has a modified monomer unit content in the range of 0.00001 to 1.0% by mass relative to the total polymerization units. The lower limit of the modified monomer unit content is more preferably 0.0001% by mass, even more preferably 0.001% by mass, even more preferably 0.005% by mass, and especially preferably 0.010% by mass. The upper limit of the modified monomer unit content is preferably 0.90% by mass, more preferably 0.50% by mass, even more preferably 0.40% by mass, even more preferably 0.30% by mass, especially preferably 0.20% by mass, and particularly preferably 0.10% by mass.
[0065] The modified monomers that can be used in the above-mentioned PTFE as fluororesin B are the same as those exemplified for PTFE (high molecular weight PTFE) as fluororesin A.
[0066] Fluororesin B is polymerized by emulsion polymerization. Fluororesin B, which is polymerized by emulsion polymerization and does not exhibit melt fluidity, may satisfy any of the following conditions, and preferably all of them. (i) The proportion of particles with a particle diameter of 1 μm or less (primary particles) obtained by scanning electron microscope (SEM) image processing is greater than 50%, preferably greater than 70%, and more preferably greater than 90%. (ii) The amount of anionic fluorine-containing surfactant measured by liquid chromatography-mass spectroscopy (LC / MS / MS) using an extract obtained by Soxhlet extraction with methanol is 1 ppb by mass or more.
[0067] The above emulsion polymerization can be carried out by known methods. For example, by carrying out emulsion polymerization of monomers necessary to constitute fluororesin B in an aqueous medium in the presence of an anionic fluorine-containing surfactant and a polymerization initiator, an aqueous dispersion containing particles (primary particles) of fluororesin B can be obtained. In the above emulsion polymerization, chain transfer agents, buffers, pH adjusters, stabilizing aids, dispersion stabilizers, etc. may be used as needed.
[0068] The above aqueous dispersion may contain a hydrocarbon surfactant. Preferably, the hydrocarbon surfactant does not contain fluorine atoms. The hydrocarbon surfactant may be one used in the emulsion polymerization, or it may be added after the emulsion polymerization.
[0069] Examples of hydrocarbon surfactants that can be used include those described in Japanese Patent Publication No. 2013-542308, Japanese Patent Publication No. 2013-542309, and Japanese Patent Publication No. 2013-542310.
[0070] Hydrocarbon surfactants have both hydrophilic and hydrophobic parts on the same molecule. These may be cationic, nonionic, or anionic.
[0071] Cationic surfactants typically have a positively charged hydrophilic portion, such as alkylated ammonium halides (e.g., alkylated ammonium bromide), and a hydrophobic portion, such as long-chain fatty acids.
[0072] Anionic surfactants typically have a hydrophilic portion, such as a carboxylate, sulfonate, or sulfate, and a hydrophobic portion, such as a long-chain hydrocarbon portion, such as an alkyl group.
[0073] Nonionic surfactants typically do not contain charged groups and have a hydrophobic moiety that is a long-chain hydrocarbon. The hydrophilic moiety of a nonionic surfactant contains water-soluble functional groups such as ethylene ether chains derived from polymerization with ethylene oxide.
[0074] The hydrocarbon-based surfactant is preferably an anionic surfactant or a nonionic surfactant.
[0075] Examples of anionic hydrocarbon surfactants include Resolution Performance Products' Versatic® 10 and BASF's Avanell S series (S-70, S-74, etc.).
[0076] As an anionic hydrocarbon surfactant, R-L-M 1 (In the formula, R is a linear or branched alkyl group having 1 or more carbon atoms which may have a substituent, or a cyclic alkyl group having 3 or more carbon atoms which may have a substituent. When the number of carbon atoms is 3 or more, it may contain a monovalent or divalent heterocyclic ring or may form a ring. L is -ArSO3 - , -SO3<00...5 These may be the same or different, and are H or an organic group having 1 to 10 carbon atoms, optionally substituted imidazolium, optionally substituted pyridinium, or optionally substituted phosphonium. -ArSO3 - Anionic surfactants, represented by aryl sulfonates, are also examples.
[0078] As anionic hydrocarbon surfactants, R 7 (-LM 1 )3(wherein, R 7 However, it is a linear or branched alkylidine group having 1 or more carbon atoms, which may have substituents, or a cyclic alkylidine group having 3 or more carbon atoms, which may have substituents, and if it has 3 or more carbon atoms, it may include a monovalent or divalent heterocycle, or it may be ring-shaped. L is -ArSO3 - , -SO3 - -SO4-, -PO3 - or -COO - And M 1 H, metal atoms, NR 5 4(R 5 These may be the same or different, and are H or an organic group having 1 to 10 carbon atoms, optionally substituted imidazolium, optionally substituted pyridinium, or optionally substituted phosphonium. -ArSO3 - Anionic surfactants, represented by aryl sulfonates, are also examples.
[0079] Examples of anionic hydrocarbon surfactants include the sulfosuccinate surfactant Lankropol® K8300 from Akzo Nobel Surface Chemistry LLC. Examples of sulfosuccinate hydrocarbon surfactants include sodium diisodecyl sulfosuccinate (Clariant's Emulsogen® SB10) and sodium diisotridecyl sulfosuccinate (Cesapinia Chemicals' Polilol® TR / LNA).
[0080] An anionic hydrocarbon surfactant is PolyFox® surfactant from Omnova Solutions, Inc. TM PF-156A, PolyFox TM Other examples include the PF-136A.
[0081] Examples of the above-mentioned nonionic surfactants include ether-type nonionic surfactants such as polyoxyethylene alkyl ethers, polyoxyethylene alkylphenyl ethers, and polyoxyethylene alkylene alkyl ethers; polyoxyethylene derivatives such as ethylene oxide / propylene oxide block copolymers; ester-type nonionic surfactants such as polyoxyethylene fatty acid esters (polyoxyethylene alkyl esters), sorbitan fatty acid esters (sorbitan alkyl esters), polyoxyethylene sorbitan fatty acid esters (polyoxyethylene sorbitan alkyl esters), polyoxyethylene sorbitol fatty acid esters, and glycerin fatty acid esters (glycerol esters); amine-based nonionic surfactants such as polyoxyethylene alkylamines and alkyl alkanolamides; and derivatives thereof. These can be used individually or in combination of two or more. The above-mentioned nonionic surfactant may be a non-fluorinated nonionic surfactant.
[0082] Examples of the above-mentioned polyoxyethylene alkyl ethers include polyoxyethylene lauryl ether, polyoxyethylene cetyl ether, polyoxyethylene stearyl ether, polyoxyethylene oleyl ether, and polyoxyethylene behenyl ether.
[0083] Examples of the above-mentioned polyoxyethylene alkylphenyl ethers include polyoxyethylene nonylphenyl ether and polyoxyethylene octylphenyl ether.
[0084] Specific examples of the polyoxyethylene fatty acid esters mentioned above include polyethylene glycol monolaurate, polyethylene glycol monooleate, and polyethylene glycol monostearate.
[0085] Examples of the above-mentioned sorbitan fatty acid esters include sorbitan monolaurate, sorbitan monopalmitate, sorbitan monostearate, and sorbitan monooleate.
[0086] Examples of the polyoxyethylene sorbitan fatty acid esters mentioned above include polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, and polyoxyethylene sorbitan monostearate.
[0087] Examples of the glycerol fatty acid esters mentioned above include glycerol monomyristate, glycerol monostearate, and glycerol monooleate.
[0088] Examples of the above derivatives include polyoxyethylene alkylamines, polyoxyethylene alkylphenyl-formaldehyde condensates, and polyoxyethylene alkyl ether phosphates.
[0089] The above-mentioned ether-type nonionic surfactant and ester-type nonionic surfactant may have an HLB value of 10 to 18.
[0090] Examples of nonionic hydrocarbon surfactants include Dow Chemical Company's Triton® X series (X15, X45, X100, etc.), Tergitol® 15-S series, Tergitol® TMN series (TMN-6, TMN-10, TMN-100, etc.), Tergitol® L series, BASF's Pluronic® R series (31R1, 17R2, 10R5, 25R4 (m~22, n~23)), T-Det series (A138), and Iconol® TDA series (TDA-6, TDA-9, TDA-10).
[0091] In the compounds constituting the above-mentioned nonionic surfactant, the hydrophobic group may be an alkylphenol group, a linear alkyl group, or a branched alkyl group, but it is preferable that the compound does not have an alkylphenol group in its structure, or does not have a benzene ring.
[0092] Among the above nonionic surfactants, those having an ether linkage (-O-) are preferred, the above-mentioned ether-type nonionic surfactants are more preferred, and polyoxyethylene alkyl ethers are even more preferred. Among the above polyoxyethylene alkyl ethers, those consisting of a polyoxyethylene alkyl ether structure having an alkyl group with 10 to 20 carbon atoms are preferred, and those consisting of a polyoxyethylene alkyl ether structure having an alkyl group with 10 to 15 carbon atoms are more preferred. The alkyl group in the above polyoxyethylene alkyl ether structure preferably has a branched structure.
[0093] The content of the hydrocarbon surfactant described above is preferably 12% by mass or less, more preferably 8% by mass or less, even more preferably 6% by mass or less, even more preferably 4% by mass or less, especially preferably 2% by mass or less, and particularly preferably 1% by mass or less, in order to produce a fluororesin composition with less discoloration and even better tensile properties. The content of the hydrocarbon surfactant described above may also be 1 ppm by mass or more, 10 ppm by mass or more, 100 ppm by mass or more, or 500 ppm by mass or more.
[0094] Fluororesin B may be provided from the above aqueous dispersion. Furthermore, by coagulating and drying the above aqueous dispersion, a powder containing particles of fluororesin B can be obtained. Fluororesin B may also be provided from this powder. Coagulation and drying can both be carried out by known methods.
[0095] The first fluororesin composition may contain particles of fluororesin B. The particles of fluororesin B may be primary particles or secondary particles of fluororesin B.
[0096] The secondary particles of the fluororesin B described above preferably have an average secondary particle diameter of 1000 μm or less, in that the handling properties of the fluororesin composition are further improved. The average secondary particle diameter is more preferably 900 μm or less, even more preferably 800 μm or less, and particularly preferably 700 μm or less. The average secondary particle diameter is also preferably 100 μm or more, more preferably 200 μm or more, even more preferably 300 μm or more, and particularly preferably 400 μm or more. The above average secondary particle diameter is measured using a Beckman Coulter laser diffraction particle size distribution analyzer (LS13 320) in a dry manner at a vacuum pressure of 20 mH2O, and is defined as being equal to the particle diameter corresponding to 50% of the integrated particle size distribution (volume-based).
[0097] The particles of the fluororesin B described above preferably have a D90 of 10 μm or more, more preferably 30 μm or more, even more preferably 50 μm or more, and also preferably 2000 μm or less, more preferably 1500 μm or less, and even more preferably 1200 μm or less, in order to further improve the handling properties of the fluororesin composition described above. The above D90 is measured using a Beckman Coulter laser diffraction particle size distribution analyzer (LS13 320) in a dry manner at a vacuum pressure of 20 mH2O, and is defined as being equal to the particle size corresponding to 90% of the integrated particle size distribution (volume-based).
[0098] The first fluororesin composition has an apparent density of 0.42 g / ml or higher. Having an apparent density within this range provides the first fluororesin composition with excellent handling properties. For superior handling, the apparent density is preferably 0.45 g / ml or higher, and more preferably 0.47 g / ml or higher. There is no particular upper limit, but it may be as high as 1.00 g / ml. The apparent density mentioned above is measured in accordance with JIS K 6891.
[0099] The content of fluororesin A in the first fluororesin composition is preferably 10 to 90% by mass relative to the fluororesin composition, in that the tensile properties are further improved. The above content is more preferably 20% by mass or more, even more preferably 30% by mass or more, even more preferably 40% by mass or more, especially preferably 50% by mass or more, particularly preferably more than 50% by mass, and more preferably 85% by mass or less, even more preferably 80% by mass or less, even more preferably less than 80% by mass, especially preferably 75% by mass or less, and particularly preferably 70% by mass or less.
[0100] The content of fluororesin B in the first fluororesin composition is preferably 10 to 90% by mass relative to the fluororesin composition, in that the tensile properties are further improved. The above content is more preferably 15% by mass or more, even more preferably 20% by mass or more, even more preferably more than 20% by mass, especially preferably 25% by mass or more, particularly preferably 30% by mass or more, and more preferably 80% by mass or less, even more preferably 70% by mass or less, even more preferably 60% by mass or less, especially preferably 50% by mass or less, and particularly preferably less than 50% by mass.
[0101] The total amount of fluororesins A and B in the first fluororesin composition is preferably 80% by mass or more, more preferably 85% by mass or more, even more preferably 90% by mass or more, even more preferably 95% by mass or more, and particularly preferably 98% by mass or more, relative to the fluororesin composition.
[0102] The first fluororesin composition contains TFE units and modified monomer units based on modified monomers copolymerizable with TFE, and preferably the amount of the modified monomer units is 1.0% by mass or less relative to the total polymer units. Furthermore, it is preferable that the amount of TFE units is 99.0% by mass or more.
[0103] The lower limit of the content of the modified monomer units in the first fluororesin composition may be 0% by mass, more preferably 0.0001% by mass, even more preferably 0.001% by mass, even more preferably 0.005% by mass, and especially preferably 0.010% by mass. The upper limit of the content of the modified monomer units is preferably 0.90% by mass, more preferably 0.50% by mass, even more preferably 0.40% by mass, even more preferably 0.30% by mass, especially preferably 0.20% by mass, and particularly preferably 0.10% by mass. The content of the above-mentioned modified monomer units can be calculated by appropriately combining NMR, FT-IR, elemental analysis, and X-ray fluorescence analysis depending on the type of monomer. Furthermore, if the raw material composition is known, it can also be calculated from that composition.
[0104] This disclosure also provides a fluororesin composition (hereinafter also referred to as the second fluororesin composition) comprising a fluororesin A that does not exhibit melt flowability and has a history of being heated to a temperature above its melting point, and a fluororesin B that does not exhibit melt flowability and is polymerized by emulsion polymerization without a history of being heated to a temperature above its melting point, and comprising TFE units and modified monomer units based on modified monomers copolymerizable with TFE. The second fluororesin composition has a specific monomer composition and, despite containing fluororesin A which has a history of being heated to a temperature above its melting point, it exhibits excellent handling properties (e.g., handling properties during transportation and compression molding). Furthermore, the second fluororesin composition has good tensile properties (e.g., tensile fracture strength, tensile fracture strain).
[0105] The second fluororesin composition preferably has one or more melting points in the temperature range below 333°C and one or more melting points in the temperature range of 333 to 360°C. The temperature range below 333°C is more preferably below 332°C, even more preferably below 331°C, preferably 100°C or higher, more preferably 140°C or higher, and even more preferably 160°C or higher. The above temperature range of 333 to 360°C is more preferably 334°C or higher, even more preferably 335°C, even more preferably 355°C or lower, and even more preferably 350°C or lower. Having melting points in the two temperature ranges mentioned above indicates that the fluororesin composition includes fluororesin A, which does not exhibit molten fluidity after being heated to a temperature above its melting point, and fluororesin B, which does not exhibit molten fluidity and has not been heated to a temperature above its melting point.
[0106] As the fluororesin A in the second fluororesin composition, the same fluororesin A as in the first fluororesin composition can be used.
[0107] As the fluororesin B in the second fluororesin composition, the same as the fluororesin B in the first fluororesin composition can be used, and modified PTFE containing polymerization units based on 99.0% by mass or more of TFE (TFE units) and polymerization units based on 1.0% by mass or less of modified monomer (modified monomer units) is preferred. The above fluororesin B may consist only of TFE units and modified monomer units. Examples of the modified monomers mentioned above include the monomers described above for modified PTFE as fluororesin B in the first fluororesin composition. The preferred range for the content of the modified monomer units is the same as the range described for the first fluororesin composition.
[0108] The composition of fluororesin B in the second fluororesin composition is the same as that of fluororesin B in the first fluororesin composition, except for its composition.
[0109] The second fluororesin composition contains TFE units and modified monomer units based on modified monomers copolymerizable with TFE. The second fluororesin composition may contain only TFE units and modified monomer units as polymerization units.
[0110] In order to further improve the handling properties and tensile properties of the fluororesin composition, the content of the modified monomer units is preferably 1.0% by mass or less relative to the total polymerization units constituting the fluororesin composition. The lower limit of the content of modified monomer units is preferably 0.00001% by mass, more preferably 0.0001% by mass, even more preferably 0.001% by mass, even more preferably 0.005% by mass, and especially preferably 0.010% by mass. The upper limit of the content of modified monomer units is preferably 0.90% by mass, more preferably 0.50% by mass, even more preferably 0.40% by mass, even more preferably 0.30% by mass, especially preferably 0.20% by mass, and particularly preferably 0.10% by mass.
[0111] The second fluororesin composition preferably contains 99.0% by mass or more of TFE units relative to the total polymerization units.
[0112] The content of polymerization units constituting the second fluororesin composition can be calculated by appropriately combining NMR, FT-IR, elemental analysis, and X-ray fluorescence analysis depending on the type of monomer. Alternatively, if the raw material composition is known, it can be calculated from that composition.
[0113] The content of fluororesins A and B in the second fluororesin composition, as well as the total amount of fluororesins A and B, are the same as those described for the first fluororesin composition.
[0114] The second fluororesin composition is preferable to have an apparent density of 0.42 g / ml or more, more preferably 0.45 g / ml or more, and even more preferably 0.47 g / ml or more, in terms of superior handling properties. There is no particular upper limit, but it may be as high as 1.00 g / ml. The apparent density mentioned above is measured in accordance with JIS K 6891.
[0115] The forms of the first and second fluororesin compositions are not particularly limited, but are preferably in powder form.
[0116] The first and second fluororesin compositions may satisfy any of the following conditions, and preferably all of them. (i) The proportion of particles with a particle diameter of 1 μm or less (primary particles) obtained by scanning electron microscope (SEM) image processing is greater than 50%, preferably greater than 70%, and more preferably greater than 90%. (ii) The amount of anionic fluorine-containing surfactant measured by liquid chromatography-mass spectroscopy (LC / MS / MS) using an extract obtained by Soxhlet extraction with methanol is 1 ppb by mass or more.
[0117] The first and second fluororesin compositions are preferable to have an angle of repose of less than 40°, more preferably less than 38°, and even more preferably less than 35°, in terms of excellent fluidity and ease of handling. The above angle of repose is obtained by setting up a funnel with a total height of 115 mm, a base diameter of φ26 mm, a base length of 35 mm, and an opening of 60° in the intake section, so that the height from the bottom of the funnel to the surface where the sample falls is 100 mm, dropping a 40 g sample from the funnel, and measuring the angle of the lower half of the pile of fallen sample with a protractor.
[0118] The first and second fluororesin compositions preferably have an average secondary particle diameter of 50 to 500 μm. More preferably, the average secondary particle diameter is 70 μm or more, even more preferably 100 μm or more, even more preferably 300 μm or less, and even more preferably 200 μm or less. The above average secondary particle diameter is measured using a Beckman Coulter laser diffraction particle size distribution analyzer (LS13 320) in a dry manner at a vacuum pressure of 20 mH2O, and is defined as being equal to the particle diameter corresponding to 50% of the integrated particle size distribution (volume-based).
[0119] The first and second fluororesin compositions preferably have a D90 of 10 μm or more, more preferably 30 μm or more, even more preferably 50 μm or more, particularly preferably 100 μm or more, and also preferably 800 μm or less, more preferably 600 μm or less, and even more preferably 500 μm or less. The above D90 is measured using a Beckman Coulter laser diffraction particle size distribution analyzer (LS13 320) in a dry manner at a vacuum pressure of 20 mH2O, and is defined as being equal to the particle size corresponding to 90% of the integrated particle size distribution (volume-based).
[0120] In terms of further improving tensile properties, the first and second fluororesin compositions preferably contain (total amount) of low molecular weight fluorine-containing compounds of 1 ppm by mass or less, more preferably 500 ppb by mass or less, even more preferably 100 ppb by mass or less, even more preferably 50 ppb by mass or less, especially preferably 25 ppb by mass or less, particularly preferably 10 ppb by mass or less, particularly more preferably 5 ppb by mass or less, especially particularly preferably 1 ppb by mass or less, and most preferably less than 1 ppb by mass. The content of the low molecular weight fluorine-containing compounds mentioned above is measured by liquid chromatography-mass spectroscopy (LC / MS / MS) after Soxhlet extraction of the sample with methanol.
[0121] Examples of the low molecular weight fluorine-containing compounds mentioned above include fluorine-containing carboxylic acids having 4 or more carbon atoms and their salts, fluorine-containing sulfonic acids having 4 or more carbon atoms and their salts, and all of these may have an ether linkage (-O-).
[0122] Examples of the low molecular weight fluorine-containing compounds mentioned above include anionic fluorine-containing surfactants. Anionic fluorine-containing surfactants may be, for example, surfactants containing fluorine atoms with a total carbon number of 20 or less in the part excluding the anionic group.
[0123] The above-mentioned anionic fluorine-containing surfactant may also be a surfactant containing fluorine with a molecular weight of 800 or less in the anionic portion. The above-mentioned "anionic portion" refers to the portion of the fluorine-containing surfactant excluding the cation. For example, F(CF2) represented by formula (I) described later. n1 In the case of COOM, "F(CF2)" n1 This is the "COO" part.
[0124] Other examples of the low molecular weight fluorine-containing compounds mentioned above include fluorine-containing surfactants with a LogPOW of 3.5 or less. The above LogPOW is the partition coefficient between 1-octanol and water, and is represented by LogP [wherein P represents the ratio of the concentration of the fluorine-containing surfactant in octanol to the concentration of the fluorine-containing surfactant in water when a 1:1 octanol / water mixture containing the fluorine-containing surfactant undergoes phase separation]. The above LogPOW is calculated by performing HPLC on standard substances with known octanol / water partition coefficients (heptanoic acid, octanoic acid, nonanoic acid, and decanoic acid) under the following conditions: column; TOSOH ODS-120T column (φ4.6 mm × 250 mm, manufactured by Tosoh Corporation), eluent; acetonitrile / 0.6 mass% HClO4 water = 1 / 1 (vol / vol%), flow rate; 1.0 ml / min, sample volume; 300 μL, column temperature; 40°C, detection light; UV 210 nm. A calibration curve is created between the elution time and the known octanol / water partition coefficient, and the LogPOW is calculated from the elution time of the sample solution using this calibration curve.
[0125] Specifically, the above-mentioned fluorine-containing surfactants include U.S. Patent Publication No. 2007 / 0015864, U.S. Patent Publication No. 2007 / 0015865, U.S. Patent Publication No. 2007 / 0015866, U.S. Patent Publication No. 2007 / 0276103, U.S. Patent Publication No. 2007 / 0117914, U.S. Patent Publication No. 2007 / 142541, U.S. Patent Publication No. 2008 / 0015319, and U.S. Patent No. 3250808. Examples include those described in the book, U.S. Patent No. 3,271,341, Japanese Patent Publication No. 2003-119204, International Publication No. 2005 / 042593, International Publication No. 2008 / 060461, International Publication No. 2007 / 046377, Japanese Patent Publication No. 2007-119526, International Publication No. 2007 / 046482, International Publication No. 2007 / 046345, U.S. Patent Application Publication No. 2014 / 0228531, International Publication No. 2013 / 189824, and International Publication No. 2013 / 189826.
[0126] The above anionic fluorine-containing surfactants include those with the following general formula (N0 ): X n0 -Rf n0 -Y 0 (N 0 ) (In the formula, X n0 Rf is H, Cl, or F. n0 This is an alkylene group having 3 to 20 carbon atoms, being linear, branched, or cyclic, in which some or all of the hydrogen atoms are substituted with fluorine, and the alkylene group may contain one or more ether bonds, and some of the hydrogen atoms may be substituted with chlorine. 0 The group is an anionic group. Examples of compounds represented by ) are shown.
[0127] Y 0 The anionic group may be -COOM, -SO2M, or -SO3M. M is H, a metal atom, NR 7 4. Imidazolium which may have substituents, pyridinium which may have substituents, or phosphonium which may have substituents, 7 is either H or an organic group. Examples of the above-mentioned metal atoms include alkali metals (Group 1) and alkaline earth metals (Group 2), such as Na, K, or Li. R 7 is H or C 1-10 The organic group may be H or C 1-4 The organic group may be H or C 1-4 It may be an alkyl group. M is H, a metal atom, or NR 7 It may be 4, and may be H, alkali metals (Group 1), alkaline earth metals (Group 2), or NR 7 It may be 4, and may be H, Na, K, Li, or NH4.
[0128] The above Rf n0 It is acceptable if 50% or more of the H atoms are replaced with fluorine.
[0129] The above general formula (N 0 Compounds represented by the following general formula (N1 ): X n0 -(CF2) m1 -Y 0 (N 1 ) (wherein, X n0 is H, Cl or F, m1 is an integer of 3 to 15, and Y 0 is as defined above.) A compound represented by the following general formula (N 2 ): Rf n1 -O-(CF(CF3)CF2O) m2 CFX n1 -Y 0 (N 2 ) (wherein, Rf n1 is a perfluoroalkyl group having 1 to 5 carbon atoms, m2 is an integer of 0 to 3, X n1 is F or CF3, and Y 0 is as defined above.) A compound represented by the following general formula (N 3 ): Rf n2 (CH2) m3 -(Rf n3 ) q -Y 0 (N 3 ) (wherein, Rf n2 is a partially or completely fluorinated alkyl group which may contain an ether bond having 1 to 13 carbon atoms and / or a chlorine atom, m3 is an integer of 1 to 3, Rf n3 is a linear or branched perfluoroalkylene group having 1 to 3 carbon atoms, q is 0 or 1, and Y 0 is as defined above.) A compound represented by the following general formula (N 4 ): Rf n4 -O-(CY n1 Y n2 ) p CF2-Y 0 (N 4 ) (wherein, Rf n4 is a linear or branched partially or completely fluorinated alkyl group which may contain an ether bond having 1 to 12 carbon atoms, and Y n1and Y n2 is, independently of one another, H or F, p is 0 or 1, and Y 0 is as defined above. A compound represented by the formula (N 5 ): [Chemical formula] (wherein X n2 , X n3 and X n4 may be the same or different and are H, F, or a linear or branched moiety which may contain an ether bond having 1 to 6 carbon atoms or a completely fluorinated alkyl group. Rf n5 is a linear or branched moiety which may contain an ether bond having 1 to 3 carbon atoms or a completely fluorinated alkylene group, L is a linking group, and Y 0 is as defined above. However, the total number of carbon atoms of X n2 , X n3 , X n4 and Rf n5 is 18 or less.) include compounds represented by the formula.
[0130] The above general formula (N 0More specifically, examples of compounds represented by the formula (I) include perfluorocarboxylic acid (I) represented by the following general formula (I), ω-H perfluorocarboxylic acid (II) represented by the following general formula (II), perfluoroether carboxylic acid (III) represented by the following general formula (III), perfluoroalkylalkylene carboxylic acid (IV) represented by the following general formula (IV), alkoxyfluorocarboxylic acid (V) represented by the following general formula (V), perfluoroalkyl sulfonic acid (VI) represented by the following general formula (VII), ω-H perfluorosulfonic acid (VII) represented by the following general formula (VII), perfluoroalkylalkylene sulfonic acid (VIII) represented by the following general formula (VIII), alkylalkylene carboxylic acid (IX) represented by the following general formula (IX), fluorocarboxylic acid (X) represented by the following general formula (X), alkoxyfluorosulfonic acid (XI) represented by the following general formula (XI), compound (XII) represented by the following general formula (XII), compound (XIII) represented by the following general formula (XIII), etc.
[0131] The above perfluorocarboxylic acid (I) is given by the following general formula (I): F(CF2) n1 COOM (I) (In the formula, n1 is an integer between 3 and 14, and M is H, a metal atom, NR) 7 4. Imidazolium which may have substituents, pyridinium which may have substituents, or phosphonium which may have substituents, 7 (where is H or an organic group.)
[0132] The above ω-H perfluorocarboxylic acid (II) is given by the following general formula (II): H(CF2) n2 COOM (II) (In the formula, n² is an integer between 4 and 15, and M is as defined above.)
[0133] The above perfluoroether carboxylic acid (III) is given by the following general formula (III): Rf 1-O-(CF(CF3)CF2O) n3 CF(CF3)COOM (III) (In the formula, Rf 1 (where n3 is a perfluoroalkyl group having 1 to 5 carbon atoms, n3 is an integer from 0 to 3, and M is as defined above.)
[0134] The above perfluoroalkylalkylene carboxylic acid (IV) is the following general formula (IV): Rf 2 (CH2) n4 Rf 3 COOM (IV) (In the formula, Rf 2 Rf is a perfluoroalkyl group having 1 to 5 carbon atoms. 3 (where n4 is a linear or branched perfluoroalkylene group having 1 to 3 carbon atoms, n4 is an integer from 1 to 3, and M is as defined above.)
[0135] The above alkoxyfluorocarboxylic acid (V) is given by the following general formula (V): Rf 4 -O-CY 1 Y 2 CF2-COOM (V) (In the formula, Rf 4 Y is a linear or branched portion that may contain ether bonds and / or chlorine atoms with 1 to 12 carbon atoms, or a fully fluorinated alkyl group. 1 and Y 2 ) are the same or different, and are represented by H or F, and M is as defined above.
[0136] The above perfluoroalkyl sulfonic acid (VI) is based on the following general formula (VI): F(CF2) n5 SO3M (VI) (In the formula, n5 is an integer between 3 and 14, and M is as defined above.)
[0137] The above ω-H perfluorosulfonic acid (VII) is given by the following general formula (VII): H(CF2) n6 SO3M (VII) (In the formula, n6 is an integer between 4 and 14, and M is as defined above.)
[0138] The above perfluoroalkylalkylene sulfonic acid (VIII) is based on the following general formula (VIII): Rf 5 (CH2) n7 SO3M (VIII) (In the formula, Rf 5 (where n7 is a perfluoroalkyl group having 1 to 13 carbon atoms, n7 is an integer from 1 to 3, and M is as defined above.)
[0139] The above alkylalkylene carboxylic acid (IX) is the following general formula (IX): Rf 6 (CH2) n8 COOM (IX) (In the formula, Rf 6 (where n8 is a linear or branched portion that may contain ether bonds with 1 to 13 carbon atoms, or a fully fluorinated alkyl group, n8 is an integer from 1 to 3, and M is as defined above.)
[0140] The above fluorocarboxylic acid (X) is given by the following general formula (X): Rf 7 -O-Rf 8 -O-CF2-COOM (X) (In the formula, Rf 7 Rf is a linear or branched portion that may contain ether bonds and / or chlorine atoms with 1 to 6 carbon atoms, or a fully fluorinated alkyl group. 8 (where M is a linear or branched portion having 1 to 6 carbon atoms or a fully fluorinated alkyl group, and M is as defined above.)
[0141] The above alkoxyfluorosulfonic acid (XI) is given by the following general formula (XI): Rf 9 -O-CY1 Y 2 CF2-SO3M (XI) (In the formula, Rf 9 Y is a partially or fully fluorinated alkyl group that may contain ether bonds between 1 to 12 carbon atoms, and may contain chlorine. 1 and Y 2 ) are the same or different, and are represented by H or F, and M is as defined above.
[0142] The above compound (XII) has the following general formula (XII): [ka] (In the formula, X 1 , X 2 and X 3 Rf is a linear or branched portion that may contain H, F and ether bonds having 1 to 6 carbon atoms, or a fully fluorinated alkyl group, and may be the same or different. 10 L is a perfluoroalkylene group having 1 to 3 carbon atoms, L is a linking group, and Y 0 It is an anionic group. ) Y 0 may be -COOM, -SO2M, or -SO3M, or -SO3M, or COOM (wherein M is as defined above). Examples of L include single bonds, moieties that may contain ether bonds with 1 to 10 carbon atoms, or fully fluorinated alkylene groups.
[0143] The above compound (XIII) has the following general formula (XIII): Rf 11 -O-(CF2CF(CF3)O) n9 (CF2O) n10 CF2COOM (XIII) (In the formula, Rf 11This is represented as follows: is a fluoroalkyl group having 1 to 5 carbon atoms and containing chlorine, n9 is an integer from 0 to 3, n10 is an integer from 0 to 3, and M is as defined above. Compound (XIII) is CF2ClO(CF2CF(CF3)O) n9 (CF2O) n10 One example is CF2COONH4 (a mixture with an average molecular weight of 750, where n9 and n10 are as defined above).
[0144] As mentioned above, examples of the above-mentioned anionic fluorine-containing surfactants include carboxylic acid-based surfactants and sulfonic acid-based surfactants.
[0145] The fluorine-containing surfactant described above may be a single fluorine-containing surfactant or a mixture containing two or more fluorine-containing surfactants.
[0146] Examples of the fluorine-containing surfactants mentioned above include compounds represented by the following formulas. The fluorine-containing surfactant may be a mixture of these compounds. F(CF2)7COOM, F(CF2)5COOM, H(CF2)6COOM, H(CF2)7COOM, CF3O(CF2)3OCHFCF2COOM, C3F7OCF(CF3)CF2OCF(CF3)COOM, CF3CF2CF2OCF(CF3)COOM, CF3CF2OCF2CF2OCF2COOM, C2F5OCF(CF3)CF2OCF(CF3)COOM, CF3OCF(CF3)CF2OCF(CF3)COOM, CF2ClCF2CF2OCF(CF3)CF2OCF2COOM, CF2ClCF2CF2OCF2CF(CF3)OCF2COOM, CF2ClCF(CF3)OCF(CF3)CF2OCF2COOM, CF2ClCF(CF3)OCF2CF(CF3)OCF2COOM, [ka] (In each formula, M is H, metal atom, NR 7 4. Imidazolium, pyridinium, or phosphonium, which may have substituents. 7 (This is defined above.)
[0147] The first and second fluororesin compositions preferably further contain fillers. This can improve mechanical properties such as abrasion resistance and compression creep resistance. Examples of the above-mentioned fillers include glass fibers, glass beads, carbon fibers, spherical carbon, carbon black, graphite, silica, alumina, mica, silicon carbide, boron nitride, titanium dioxide, bismuth oxide, cobalt oxide, molybdenum disulfide, bronze, gold, silver, copper, nickel, aromatic polyester, polyimide, and polyphenylene sulfide, and one or more of these can be used. In particular, at least one selected from the group consisting of glass fiber, carbon fiber, graphite, and bronze is preferred.
[0148] The content of the above-mentioned filler is preferably 0 to 80% by mass relative to the above-mentioned fluororesin composition. More preferably, the content is 1% by mass or more, even more preferably 5% by mass or more, even more preferably 10% by mass or more, particularly preferably 12% by mass or more, more preferably 70% by mass or less, even more preferably 60% by mass or less, even more preferably 50% by mass or less, especially preferably 40% by mass or less, particularly preferably 30% by mass or less, and most preferably 25% by mass or less.
[0149] The first and second fluororesin compositions can be produced, for example, by mixing powder of fluororesin A with particles of fluororesin B.
[0150] The particles of fluororesin B may be mixed with fluororesin A powder in powder form, or with fluororesin A powder in aqueous dispersion form. However, it is preferable to mix them with fluororesin A powder in powder form, as this yields a fluororesin composition with superior handling properties and tensile strength.
[0151] The above mixing can be carried out, for example, using a crusher equipped with rotating blades. An example of a crusher equipped with rotating blades is the Wonder Crusher WC-3 manufactured by Osaka Chemical Co., Ltd. When mixing using the above-mentioned pulverizer, it is preferable to set the blade rotation speed to 1500 to 10000 rpm. By setting the rotation speed within this range, the shear force during mixing can be reduced, and the fibrous formation of fluororesin B can be suppressed, resulting in a fluororesin composition with high apparent density and excellent handling properties. When fluororesin B is a homopolymer of TFE, it is preferable to set the rotation speed to 1500 to 2500 rpm.
[0152] Furthermore, by granulating the mixed fluororesin composition, a fluororesin composition with high apparent density and excellent handling properties can be obtained. In this embodiment, the mixing may be carried out under conditions that facilitate the fiber formation of fluororesin B. Known methods for the above-mentioned granulation include underwater granulation, hot water granulation, emulsified dispersion granulation, emulsified hot water granulation, solvent-free granulation, and dry solvent granulation.
[0153] The obtained fluororesin composition may be pulverized. This pulverization can be carried out by known methods, for example, using a pulverizer such as an air jet mill, hammer mill, force mill, stone mill type pulverizer, or freeze pulverizer.
[0154] The first and second fluororesin compositions preferably have a tensile breaking strength of 10 MPa or more, more preferably 15 MPa or more, even more preferably 17 MPa or more, and particularly preferably 20 MPa or more. There is no upper limit, but it may be, for example, 30 MPa. The tensile breaking strength described above is measured in accordance with ASTM D1708 using a dumbbell made by punching out a molded body that has been fired by the following process: 35g of the above fluororesin composition is placed in a φ100mm mold, compression molded at a pressure of 30MPa for 1 minute, the temperature is raised from room temperature to 300°C in 3 hours, then raised from 300°C to 370°C in 4 hours, held at 370°C for 12 hours, then cooled down to 300°C in 5 hours, and finally cooled down to room temperature in 1 hour.
[0155] The first and second fluororesin compositions preferably have a tensile fracture strain of 150% or more, more preferably 200% or more, even more preferably 300% or more, and particularly preferably 330% or more. There is no particular upper limit, but it may be, for example, 600%. The tensile fracture strain described above is measured in accordance with ASTM D1708 using a dumbbell made by punching out a molded body that has been fired by the following process: 35g of the above fluororesin composition is placed in a φ100mm mold, compression molded at a pressure of 30MPa for 1 minute, heated from room temperature to 300°C in 3 hours, then heated from 300°C to 370°C in 4 hours, held at 370°C for 12 hours, then cooled down to 300°C in 5 hours, and finally cooled down to room temperature in 1 hour.
[0156] The first and second fluororesin compositions can be suitably used as molding materials. Methods for molding the above fluororesin compositions are not particularly limited, but include compression molding, ram extrusion, isostatic molding, etc. Among these, compression molding is preferred. The first and second fluororesin compositions are preferably powders for compression molding.
[0157] This disclosure also provides molded articles obtained by compression molding and firing the first and second fluororesin compositions. The molded articles of this disclosure exhibit excellent tensile properties despite containing a fluororesin that has been heated to a temperature above its melting point.
[0158] The above compression molding can be carried out, for example, by holding a pressure of 10 to 50 MPa for 1 minute to 30 hours.
[0159] The above firing process can be carried out, for example, by heating at a temperature of 350-380°C for 0.5-50 hours.
[0160] The molded articles of this disclosure preferably have a tensile breaking strength of 10 MPa or more, more preferably 15 MPa or more, even more preferably 17 MPa or more, and particularly preferably 20 MPa or more. The upper limit is not particularly limited, but may be, for example, 30 MPa. The above tensile breaking strength shall be measured in accordance with ASTM D1708.
[0161] The molded articles of this disclosure preferably have a tensile fracture strain of 150% or more, more preferably 200% or more, even more preferably 300% or more, and particularly preferably 330% or more. The upper limit is not particularly limited, but may be, for example, 600%. The tensile fracture strain mentioned above shall be measured in accordance with ASTM D1708.
[0162] Molded articles obtained from the first and second fluororesin compositions can be suitably used for lining sheets, packings, gaskets, diaphragm valves, heat-resistant wires, heat-resistant insulating tapes for vehicle motors and generators, release sheets, sealing materials, casings, sleeves, bellows, hoses, piston rings, butterfly valves, rectangular tanks, wafer carriers, and the like.
[0163] Although embodiments have been described above, it should be understood that various modifications to the form and details are possible without departing from the spirit and scope of the claims. [Examples]
[0164] The present disclosure will now be further described with reference to examples, but the present disclosure is not limited to these examples.
[0165] Various physical properties were measured using the following method.
[0166] (Melting point) The melting point was determined by performing differential scanning calorimetry (DSC) at a heating rate of 10°C / min using an X-DSC7000 (manufactured by Hitachi High-Tech Science Corporation) and identifying the temperature corresponding to the minimum point in the heat of fusion curve. If there were two or more minimum points in a single melting peak, each was considered the melting point.
[0167] (Monomer composition of fluororesins) 19 The results were measured by 1F-NMR.
[0168] (Secondary particle size of powder) The particle size distribution was determined using a Beckman Coulter laser diffraction particle size analyzer (LS13 320) in a dry manner with a vacuum pressure of 20 mH2O, based on the obtained volume-based particle size distribution. The average secondary particle diameter was defined as equal to the particle diameter corresponding to 50% of the integrated particle size distribution. The particle diameter corresponding to 10% was defined as D10, and the particle diameter corresponding to 90% was defined as D90.
[0169] (apparent density) Measurements were taken in accordance with JIS K 6891.
[0170] (Standard specific gravity (SSG)) Samples were prepared according to ASTM D4895 89 and measured using the water displacement method according to ASTM D 792.
[0171] (Angle of repose) A funnel with a total height of 115 mm, a base diameter of φ26 mm, a base length of 35 mm, and an opening of 60° was set up so that the height from the bottom of the funnel to the surface where the sample fell was 100 mm. A 40 g sample was dropped from the funnel, and the angle of the lower half of the pile of fallen sample was measured with a protractor and defined as the angle of repose.
[0172] (Monomer composition of fluororesin composition) It was calculated from the raw material composition.
[0173] (Tensile test) A molded product was obtained by firing a process in which 35g of powder was placed in a φ100mm mold, compressed under a pressure of 30MPa for 1 minute, heated from room temperature to 300°C in 3 hours, then heated from 300°C to 370°C in 4 hours, held at 370°C for 12 hours, then cooled down to 300°C in 5 hours, and finally cooled down to room temperature in 1 hour. Dumbbells were prepared by punching out these molded products, and tensile tests were performed in accordance with ASTM D 1708 to measure the tensile breaking strength and tensile breaking strain.
[0174] (Low molecular weight fluorine-containing compound content) 1 g of fluororesin composition (powder) was weighed, and 10 mL of a 0.3% ammonium hydroxide methanol solution (A) prepared with ammonia water and methanol was added. The sample bottle was placed in an ultrasonic cleaner heated to 60°C and subjected to ultrasonic treatment for 2 hours to obtain an extract. Fluorine-containing compounds in the extract were measured using a liquid chromatograph-mass spectrometer (Agilent 1290 Infinity II LC and 6530 time-of-flight mass spectrometer). The instrument configuration and measurement conditions are shown in Table 1. Compounds that could be identified as fluorine compounds with a molecular weight of 800 or less from the precise mass were extracted as peaks, and an extract chromatogram was drawn. Using an aqueous solution of perfluorooctanoic acid with known concentration, aqueous solutions with four levels of content were prepared, and each aqueous solution with its respective content was analyzed. The content and its relationship to the area area were plotted, and a calibration curve was drawn. Using the calibration curve described above, the content of fluorine-containing compounds with a molecular weight of 800 or less in the extract was calculated in terms of perfluorooctanoic acid using the extraction chromatogram and calibration curve described above.
[0175] [Table 1]
[0176] Synthesis Example 1 (Synthesis of Ammonium Perfluoroether Carboxylate Salt A) After purging a 1L autoclave with nitrogen, 16.5g of dehydrated tetramethylurea and 220g of diethylene glycol dimethyl ether were charged and cooled. 38.5g of carbonyl fluoride was then added, followed by 100g of hexafluoropropylene oxide, and the mixture was stirred. Subsequently, another 38.5g of carbonyl fluoride and 100g of hexafluoropropylene oxide were added. Then, equal amounts of carbonyl fluoride and hexafluoropropylene oxide were added again. After the reaction was complete, the reaction mixture was removed and separated to obtain the reaction product in the lower layer.
[0177] 1000 mL of tetraglyme and 75 g of CsF were placed in a 6 L autoclave, and the autoclave was purged with nitrogen. The autoclave was then cooled, and 2100 g of the reaction product obtained above was charged. Hexafluoropropylene oxide was then introduced into the autoclave to start the reaction. Finally, 1510 g of hexafluoropropylene oxide was charged. The contents were then withdrawn, and the upper and lower layers were separated using a separatory funnel. The upper layer weighed 1320 g and the lower layer weighed 3290 g. The lower layer was rectified and isolated.
[0178] Next, 1000 g of the isolated target product was added to 1000 g of pure water and hydrolysis was performed. Then, the organic layer (lower layer) was collected by liquid-liquid separation using a separatory funnel. The collected solution was washed with sulfuric acid water. The obtained solution was further purified by simple distillation. After purification, 500 g of the simple distillate obtained above was added dropwise to an aqueous solution prepared by mixing the obtained compound with 76 g of 28% by mass aqueous ammonia solution and 600 g of pure water. After the dropwise addition was complete, 28% by mass aqueous ammonia solution was added to adjust the pH to 7. This was freeze-dried to obtain perfluoroether carboxylate ammonium salt A.
[0179] Manufacturing Example 1 (Preparation of fluororesin powder A-1) Using 35 g of PTFE molding powder (standard specific gravity (SSG): 2.159, melting point: 345.0℃) obtained by crushing coarse homo-PTFE powder, which was obtained by suspension polymerization of TFE monomer alone, in a pulverizer, a molded product was obtained by compression molding in a φ100 mm mold under conditions of 30 MPa for 1 minute and firing at 370℃ for 3 hours. After cutting the obtained molded product, it was pulverized in a pulverizer to obtain fluororesin powder A-1. The melting point of fluororesin powder A-1 was 328℃, the average secondary particle diameter was 23 μm, D10 was 8 μm, D90 was 48 μm, and the apparent density was 0.64 g / ml.
[0180] Manufacturing Example 2 (Preparation of Fluororesin Powder A-2) The molded product obtained in the same manner as in Production Example 1 was cut and then pulverized in a pulverizer to obtain fluororesin powder A-2. The melting point of fluororesin powder A-2 was 328°C, the average secondary particle size was 37 μm, D10 was 7 μm, D90 was 87 μm, and the apparent density was 0.53 g / ml.
[0181] Manufacturing Example 3 (Preparation of Fluororesin Powder B-1) In a 6L SUS autoclave equipped with stirring blades, an aqueous dispersion of homo-PTFE consisting solely of TFE units was obtained using a known emulsion polymerization method with ammonium perfluoroethercarboxylate salt A. This dispersion was then coagulated and dried using a known method to obtain fluororesin powder B-1. The obtained fluororesin powder B-1 had an apparent density of 0.45 g / ml, an average secondary particle size of 540 μm, a standard specific gravity (SSG) of 2.172, and melting points of 338.6°C and 343.5°C.
[0182] Manufacturing Example 4 (Preparation of Fluororesin Powder B-2) In a 6L SUS autoclave equipped with stirring blades, an aqueous dispersion of modified PTFE consisting of TFE units and perfluoro(propyl vinyl ether) (PPVE) units was obtained by a known emulsion polymerization method using ammonium perfluoroether carboxylate A. The dispersion was then coagulated and dried by a known method to obtain fluororesin powder B-2. The obtained fluororesin powder B-2 had an apparent density of 0.46 g / ml, an average secondary particle diameter of 460 μm, a standard specific gravity (SSG) of 2.169, a melting point of 334.6 °C, and a PPVE unit content of 0.14 mass%.
[0183] Example 1 PTFE powder (fluororesin composition) was obtained by mixing 50g of fluororesin powder A-1 and 50g of fluororesin powder B-1 using a Wonder Crusher WC-3 at a rotation speed of 1900 rpm for 60 seconds. The obtained PTFE powder had an average secondary particle diameter of 422 μm, D10 of 27 μm, D90 of 787 μm, apparent density of 0.48 g / ml, and angle of repose of 37°, and exhibited excellent handling properties. Furthermore, the above PTFE powder contained 100% by mass of TFE units relative to the total polymerization units. The melting points of the above PTFE powder were 329°C, 339°C, and 344°C, the tensile breaking strength was 13 MPa, and the tensile breaking strain was 199%.
[0184] Example 2 PTFE powder was obtained in the same manner as in Example 1, except that fluororesin powder B-1 was changed to fluororesin powder B-2 and the rotation speed was changed to 2900 rpm. The obtained PTFE powder had an average secondary particle diameter of 177 μm, D10 of 22 μm, D90 of 421 μm, apparent density of 0.46 g / ml, and angle of repose of 36°, and exhibited excellent handling properties. Furthermore, the above PTFE powder contained 99.93% by mass of TFE units and 0.07% by mass of PPVE units relative to the total polymerization units. The melting points of the above PTFE powder were 329°C and 336°C, the tensile breaking strength was 24 MPa, the tensile breaking strain was 439%, and the content of low molecular weight fluorine-containing compounds (fluorine-containing surfactants with a molecular weight of 800 or less in the anionic portion) was 1 ppm by mass or less.
[0185] Comparative Example 1 A PTFE powder was obtained in the same manner as in Example 1 except that the rotational speed was changed to 2900 rpm. The average secondary particle diameter of the obtained PTFE powder was 341 μm, D10 was 31 μm, D90 was 717 μm, the apparent density was 0.39 g / ml, and the angle of repose was 41°, indicating poor handling properties. The melting points of the above PTFE powder were 329 °C and 339 °C, the tensile breaking strength was 19 MPa, and the tensile breaking strain was 321%.
[0186] Comparative Example 2 When a tensile test was conducted in the same manner as in Example 1 using only 35 g of fluororesin powder A-1 (angle of repose = 21°, melting point 328 °C), the tensile breaking strength was 9 MPa and the tensile breaking strain was 145%.
[0187] Example 3 A PTFE powder was obtained in the same manner as in Example 2 except that 70 g of fluororesin powder A-1 was changed to 70 g and 30 g of fluororesin powder B-2, and the rotational speed was changed to 6900 rpm. The average secondary particle diameter of the obtained PTFE powder was 44 μm, D10 was 12 μm, D90 was 158 μm, the apparent density was 0.44 g / ml, and the angle of repose was 39°, indicating excellent handling properties. Further, the above PTFE powder contained 99.958 mass% of TFE units and 0.042 mass% of PPVE units with respect to all polymerization units. The melting points of the above PTFE powder were 329 °C and 336 °C, the tensile breaking strength was 21 MPa, and the tensile breaking strain was 454%.
[0188] Example 4 A PTFE powder was obtained in the same manner as in Example 2 except that 40 g of fluororesin powder A-1, 45 g of fluororesin powder B-2, and 15 g of glass fiber (PFE-001 manufactured by Nitto Boseki Co., Ltd.) were used. The apparent density of the obtained PTFE powder was 0.43 g / ml, and the angle of repose was 35°, indicating excellent handling properties. Further, the above PTFE powder contained 99.937 mass% of TFE units and 0.063 mass% of PPVE units with respect to all polymerization units. The melting points of the above PTFE powder were 329 °C and 336 °C, the tensile breaking strength was 15 MPa, and the tensile breaking strain was 386%.
[0189] Example 5 PTFE powder was obtained in the same manner as in Example 3, using 40 g of fluororesin powder A-1, 45 g of fluororesin powder B-2, and 15 g of bronze powder (Bro-AT-200 manufactured by Fukuda Metal Foil & Powder Industry). The obtained PTFE powder had an apparent density of 0.46 g / ml and an angle of repose of 33°, and exhibited excellent handling properties. Furthermore, the above PTFE powder contained 99.937 mass% of TFE units and 0.063 mass% of PPVE units relative to the total polymerization units. The melting points of the above PTFE powder were 329°C and 336°C, the tensile breaking strength was 15 MPa, and the tensile breaking strain was 400%.
[0190] Example 6 PTFE powder was obtained in the same manner as in Example 3, except that fluororesin powder A-1 was replaced with fluororesin powder A-2. The apparent density was 0.43 g / ml, the angle of repose was 38°, and it had excellent handling properties. The above PTFE powder contained 99.93% by mass of TFE units and 0.07% by mass of PPVE units relative to the total polymerization units. The melting points of the above PTFE powder were 329°C and 336°C, the tensile breaking strength was 26 MPa, and the tensile breaking strain was 393%.
[0191] Example 7 The PTFE powder obtained in Comparative Example 1 was granulated using an AS ONE PZ-02R pan-type granulator by adding 10 g of methanol to 100 g of PTFE powder and rotating at 24 revolutions per minute for 20 minutes to obtain PTFE powder. The obtained PTFE powder had an apparent density of 0.60 g / ml and an angle of repose of 10°, and was easy to handle. The melting points of the above PTFE powder were 329°C and 339°C, the tensile breaking strength was 15 MPa, and the tensile breaking strain was 306%.
Claims
1. A fluororesin composition comprising: fluororesin A which has a history of being heated to a temperature equal to or higher than its melting point and does not exhibit melt fluidity; and fluororesin B which has no history of being heated to a temperature equal to or higher than its melting point and which does not exhibit melt fluidity and has been polymerized by emulsion polymerization, and has an apparent density of 0.42 g / ml or more.
2. 2. The fluororesin composition according to claim 1, wherein the fluororesin A is polytetrafluoroethylene.
3. A fluororesin composition according to claim 1 or 2, wherein the content of fluororesin A in the fluororesin composition is 40 mass% or more.
4. A fluororesin composition according to any one of claims 1 to 3, wherein the content of fluororesin A in the fluororesin composition is 50 mass% or more.
5. A fluororesin composition according to any one of claims 1 to 4, wherein the D90 of the fluororesin A is 10 μm or more and 600 μm or less.
6. A fluororesin composition described in any of claims 1 to 5, wherein the fluororesin A is pulverized by at least one type of pulverizer selected from the group consisting of an air jet mill, a hammer mill, a force mill, and a stone-mill type pulverizer.
7. The fluororesin composition according to any one of claims 1 to 6, which has one or more melting points in a temperature range below 333°C and one or more melting points in a temperature range of 333 to 360°C.
8. The fluororesin composition according to any one of claims 1 to 7, which has an angle of repose of less than 40°.
9. The fluororesin composition according to any one of claims 1 to 8, wherein the average secondary particle size is 50 to 500 µm.
10. A fluororesin composition according to any one of claims 1 to 9, wherein D90 is 10 μm or more and 800 μm or less.
11. The fluororesin composition according to claim 1, wherein D10 is 12 μm or more and 27 μm or less.
12. A fluororesin composition according to any one of claims 1 to 11, further comprising a low molecular weight fluorine-containing compound, the content of said low molecular weight fluorine-containing compound being 1 ppm by mass or less relative to said fluororesin composition.
13. The fluororesin composition according to any one of claims 1 to 12, comprising tetrafluoroethylene units and modified monomer units based on a modified monomer copolymerizable with tetrafluoroethylene, and an amount of the modified monomer units relative to all polymerized units is 1.0 mass% or less.
14. The fluororesin composition according to any one of claims 1 to 13, which is in the form of a powder.
15. The fluororesin composition according to claim 1, which is a powder for compression molding at a pressure of 50 MPa or less.
16. The fluororesin composition according to any one of claims 1 to 15, having a tensile break strength of 10 MPa or more.
17. The fluororesin composition according to any one of claims 1 to 16, which has a tensile break strain of 150% or more.
18. A fluororesin composition according to any one of claims 1 to 17, having a tensile breaking strain of 330% or more.
19. The fluororesin composition according to any one of claims 1 to 18, which is granulated.
20. The fluororesin composition according to any one of claims 1 to 19, further comprising a filler.
21. The fluororesin composition according to any one of claims 1 to 20, which is used for at least one selected from the group consisting of lining sheets, packings, gaskets, diaphragm valves, heat-resistant electric wires, heat-resistant insulating tapes, release sheets, sealing materials, casings, sleeves, bellows, hoses, piston rings, butterfly valves, square tanks, and wafer carriers.
22. A molded article obtained by compression molding and sintering the fluororesin composition according to any one of claims 1 to 21.
23. The fluororesin composition includes a fluororesin A that has a history of being heated to a temperature equal to or higher than its melting point and does not exhibit melt fluidity, and a fluororesin B that has no history of being heated to a temperature equal to or higher than its melting point and does not exhibit melt fluidity which has been polymerized by emulsion polymerization, and includes tetrafluoroethylene units and modified monomer units based on a modified monomer copolymerizable with tetrafluoroethylene.
24. The fluororesin composition according to claim 23, having an apparent density of 0.42 g / ml or more.
25. A fluororesin composition according to claim 23 or 24, comprising, relative to all polymerization units constituting the fluororesin composition, 99.0 mass% or more of tetrafluoroethylene units and 0.010 to 0.10 mass% of modified monomer units, and the modified monomer is at least one selected from the group consisting of perfluoroolefins, perhaloolefins, perfluorovinyl ethers and perfluoroallyl ethers.
26. The fluororesin composition according to any one of claims 23 to 25, which is used for at least one selected from the group consisting of lining sheets, packings, gaskets, diaphragm valves, heat-resistant electric wires, heat-resistant insulating tapes, release sheets, sealing materials, casings, sleeves, bellows, hoses, piston rings, butterfly valves, square tanks, and wafer carriers.